Enrichment of the Glycyrrhizic Acid from Licorice Roots (Glycyrrhiza glabra L.) by Isoelectric Focused Adsorptive Bubble Chromatography - Eyyüp Karaoğul; Perihan Parlar; Harun Parlar; M. Hakkı Alma (Journal of Analytical Methods in Chemistry)
The main aim of this study was to enrich glycyrrhizic acid ammonium salt known as one of the main compounds of licorice roots (Glycyrrhiza glabra L.) by isoelectric focused adsorptive bubble separation technique with different foaming agents. In the experiments, four bubble separation parameters were used with β-lactoglobulin, albumin bovine, and starch (soluble) preferred as foaming agents and without additives. The enrichment of glycyrrhizic acid ammonium salt into the foam was influenced by different additive substances. The results showed that highest enrichment values were obtained from β-lactoglobulin as much as 368.3 times. The lowest enrichment values (5.9 times) were determined for the application without additive. After enrichment, each experiment of glycyrrhizic acid ammonium salt confirmed that these substances could be quantitatively enriched into the collection vessel with isoelectric focused adsorptive bubble separation technique. The transfer of glycyrrhizic acid ammonium salt into the foam from standard solution in the presence of additive was more efficient than aqueous licorice extract.